2017
DOI: 10.1152/ajpgi.00169.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Consumption of a high-iron diet disrupts homeostatic regulation of intestinal copper absorption in adolescent mice

Abstract: High-iron feeding of rodents has been commonly used to model human iron-overload disorders. We recently noted that high-iron consumption impaired growth and caused severe systemic copper deficiency in growing rats, but the mechanism by which this occurred could not be determined due to technical limitations. In the current investigation, we thus utilized mice; first to determine if the same phenomenon occurred in another mammalian species, and secondly since we could assess in vivo copper absorption in mice. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
4
35
0
Order By: Relevance
“…Copper deficiency has not been reported in hemochromatosis, which is an autosomal recessive disease characterized by increased intestinal iron absorption. Excessive dietary iron ingestion caused sever copper deficiency in mice [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Copper deficiency has not been reported in hemochromatosis, which is an autosomal recessive disease characterized by increased intestinal iron absorption. Excessive dietary iron ingestion caused sever copper deficiency in mice [21]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, immunoreactive CP was reported to be decreased in hereditary hemochromatosis (HH), a genetic iron-loading disorder (67). Additional recent investigations in rats (112) and mice (110) demonstrated that high-iron intake can lead to copper depletion. In these studies, high-iron fed rodents developed severe copper deficiency-related pathologies, including growth retardation, cardiac hypertrophy, anemia, and impaired production of the liver-derived circulating FOX CP, which is a biomarker of moderate to severe copper deficiency (110, 112).…”
Section: Intersection Of Iron and Copper Metabolism In The Intestinementioning
confidence: 98%
“…Additional recent investigations in rats (112) and mice (110) demonstrated that high-iron intake can lead to copper depletion. In these studies, high-iron fed rodents developed severe copper deficiency-related pathologies, including growth retardation, cardiac hypertrophy, anemia, and impaired production of the liver-derived circulating FOX CP, which is a biomarker of moderate to severe copper deficiency (110, 112). Increasing dietary Cu prevented the development of these pathologies in rats, proving that copper deficiency was the underlying cause (112).…”
Section: Intersection Of Iron and Copper Metabolism In The Intestinementioning
confidence: 98%
See 1 more Smart Citation
“…Many of these pathological symptoms typify severe copper deficiency (2,3). Notably, these abnormalities did not occur in animals consuming the high-iron diet with excess copper (4,5), essentially proving that these pathologies were caused by copper depletion. The threshold of dietary iron necessary to disrupt copper metabolism has not, however, been experimentally determined.…”
Section: Introductionmentioning
confidence: 94%